Stem Cells in Solid Tumors: Accumulated Evidence and Future Directions - Deepthi Venkatachalapathy; Parveen Doddamani; Aradya V Hirriyannaiah; Prashant Vishwanath; Suma Nataraj; Akila Prashant (Indian Journal of Medical Biochemistry)
Cancer stands as a leading global cause of human mortality, predominantly driven by solid tumors that can ravage vital organs. The scientific community has made significant strides in comprehending the molecular and cellular underpinnings of cancer. However, translating these discoveries into effective, targeted therapeutics has proven challenging. This gap highlights the existence of critical bottlenecks hindering the journey from fundamental research findings to fully realized anticancer drugs. Recent insights into cancer biology have illuminated one potential bottleneck: the presence of cancer stem cells (CSCs). These represent a minority subset of cells within a tumor, believed to orchestrate the relentless growth of the entire tumor. The concept of CSCs has gained substantial traction, thanks to advancements in stem cell research. Developing more potent and precise cancer therapies hinges on our ability to identify and understand these cancer-initiating cells within solid tumors. It is essential to discern how CSCs differ from other cancer cells coexisting in the same tissue. This review endeavors to compile the accumulated scientific evidence supporting the existence of CSCs, elucidate the cell surface markers employed for their isolation, dissect the pathways governing their self-renewal and differentiation, and outline future directions for harnessing them as therapeutic targets to eradicate tumor growth comprehensively.